GABAergic neurons in basal forebrain exert frequency-specific modulation on auditory cortex and enhance attentional selection of auditory stimuli - Kevin Thomas; Hamid Azimi; Davide Maggioni; Mark Sanders; Pilar Vaca Sánchez; Michael A. Harvey; Gregor Rainer (Communications Biology)
Abstract The basal forebrain (BF), in particular its cholinergic projections to cortex, has been implicated in regulation of attention in sensory systems. Here, we examine the role of GABAergic projections of the posterior nucleus basalis (pNB) and globus pallidus (GP) in attentional regulation in the auditory system. We employed a detection task where rats detected a narrow band target embedded in broad band noise, while optogenetically modulating GABAergic BF activity. We found that GABAergic BF modulation impacted target detection specifically close to perceptual threshold, consistent with a role in attentional modulation. We also present evidence for target frequency specificity of this modulation, including frequency selectivity and tonotopic organization of pNB/GP, as well as frequency band specific effects of optogenetics on behavioural target detection and on neural activity in auditory cortex and thalamus. Our findings highlight an important role of BF GABAergic neurons in modulating attention in the auditory pathway.